Costs of missed work among employed people with inflammatory bowel disease: a cross-sectional population-representative study. (2022) - Kuenzig, Ellen; Lebenbaum, Michael; Mason, Joyce; Vyas, Manav; Kaplan, Gilaad; Murthy, Sanjay; Targownik, Laura; Benchimol, Eric
No abstract available